Mortality among twins and singletons in sub-Saharan Africa between 1995 and 2014: a pooled analysis of data from 90 Demographic and Health Surveys in 30 countries - Monden, CWS; Smits, J (Elsevier, 2017)
Sub-Saharan Africa has the world's highest under-5 and neonatal mortality rates as well as the highest naturally occurring twin rates. Twin pregnancies carry high risk for children and mothers. Under-5 mortality has declined in sub-Saharan Africa over the last decades. It is unknown whether twins have shared in this reduction.We pooled data from 90 Demographic and Health Surveys for 30 sub-Saharan Africa countries on births reported between 1995 and 2014. We used information on 1 685 110 singleton and 56 597 twin livebirths to compute trends in mortality rates for singletons and twins. We examined whether the twin-singleton rate ratio can be attributed to biological, socioeconomic, care-related factors, or birth size, and estimated the mortality burden among sub-Saharan African twins.Under-5 mortality among twins has declined from 327·7 (95% CI 312·0-343·5) per 1000 livebirths in 1995-2001 to 213·0 (196·7-229·2) in 2009-14. This decline of 35·0% was much less steep than the 50·6% reduction among singletons (from 128·6 [95% CI 126·4-130·8] per 1000 livebirths in 1995-2001 to 63·5 [61·6-65·3] in 2009-14). Twins account for an increasing share of under-5 deaths in sub-Saharan Africa: currently 10·7% of under-5 mortality and 15·1% of neonatal mortality. We estimated that about 315 000 twins (uncertainty interval 289 000-343 000) die in sub-Saharan African each year. Excess twin mortality cannot be explained by common risk factors for under-5 mortality, including birthweight. The difference with singletons was especially stark for neonatal mortality (rate ratio 5·0, 95% CI 4·5-5·6). 51·7% of women pregnant with twins reported receiving medical assistance at birth.The fate of twins in sub-Saharan Africa is lagging behind that of singletons. An alarming one-fifth of twins in the region dies before age 5 years, three times the mortality rate among singletons. Twins account for a substantial and growing share of under-5 and neonatal mortality, but they are largely neglected in the literature. Coordinated action is required to improve the situation of this extremely vulnerable group.None.